Analisis Dampak Penggunaan Bahan Bakar Alternatif dengan Metode Life Cycle Assessment di Pabrik Semen Tuban - Rafi Yogatama Indriyantono; Yayok Suryo Purnomo (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The cement sector has greatly added to the overall emissions discharged into the atmosphere., with coal usage as a fuel source being considered a factor in environmental impacts. Therefore, with the increasing global demand for cement, preventive measures are needed to reduce total air emissions and provide appropriate improvement recommendations. The use of alternative fuels is considered a solution to mitigate these impacts, but it also introduces new challenges, such as determining the extent of emissions contributed to the environment and other resulting impacts from the utilization of alternative energy sources. Life Cycle Assessment (LCA) method is used in this study for identification and analysis of environmental impacts. SimaPro 9.5 software, utilizing the IMPACT 2002+ impact assessment method, is employed for analysis. The LCA impact analysis results indicate that respiratory inorganics, global warming potential, and terrestrial ecotoxicity are the three highest impacts resulting from air emissions, including NOx, Particulates, SO2, CO2, CO, Cd, Cu, Hg, and Cr due to the utilization of fuels such as coal, rice husks, industrial diesel oil (IDO), spent earth, cocopeat, and tobacco waste. Recommendations for improvement include increasing the ratio of rice husk usage by 15%-30% as fuel and planting giant miscanthus grass (miscanthus giganteus).